Analisis Pengaturan Penjualan Obat Bebas dan Obat Bebas Terbatas di Warung dan Toko Kelontong Berdasarkan Undang-Undang Kesehatan - Toyib, Toyib; Linda, Maura; Agus, Tri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Public health is a critical component of national development and a fundamental humanright, as stated in the 1945 Constitution of the Republic of Indonesia. Law Number 17 of2023 on Health categorizes drugs into two main types: prescription and non-prescription. In Indonesia, over-the-counter and limited over-the-counter drugs arefrequently sold in small shops and grocery stores. This practice stems from a lack ofpublic awareness regarding regulations governing pharmaceutical service locations, theauthority of pharmaceutical personnel, and standardized distribution channels, compounded by insufficient government oversight. This study aims to conduct a juridicalanalysis of the sale of over-the-counter and limited over-the-counter drugs in smallshops and grocery stores based on the Health Act. The research employed a normativejuridical approach. Article 145 of Law No. 17 of 2023 on Health mandates that over-the-counter and limited over-the-counter drugs must be sourced from pharmaceuticalservice facilities or other authorized outlets, such as hypermarkets, supermarkets, and andminimarkets. Furthermore, Article 436 imposes a criminal penalty of up to IDR200.000.000 on individuals without the proper authority and expertise in pharmaceuticalservices, while Article 439 stipulates imprisonment of up to 5 years or a maximum fineof IDR 500.000.000. Effective law enforcement and supervision by the National Agencyof Drug and Food Control (BPOM), alongside consumer protection, are essential inmaintaining the quality and safety of medications. Although oversight in small shops andgrocery stores is limited, the existing regulatory framework aims to mitigate risks andensure that the drugs in circulation adhere to safety and quality standards.